(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
The Catholic Church and abuses in the reform of canonical criminal law: the still uncertain appeal of secular law ABSTRACT: Sanctioning clergy abuse without denying the soul of canonical criminal law is a challenge that the Catholic Church has been confronted with for two decades now, ever since John Paul II promulgated the Apostolic Letter Sacramentorum Sanctitatis Tutela in 2001 intending to combat this scourge. This process has recently resulted in the reform of Book VI of the Code of Canon Law. In investigating the new elements introduced by this reform, this contribution questions the relationship between canon law and secular criminal law. SOMMARIO: 1. Sanzionare gli abusi senza rinnegare l’anima del diritto penale canonico - 2. Dagli scandali alla certezza della pena: nuovi principi a garanzia dell’effettività del diritto penale della Chiesa - 3. Le fattispecie: un’attenzione crescente per i diritti inviolabili della persona - 4. Sulla natura e la funzione dello ius Ecclesiae in dialogo con lo “ius civile”.